Public key infrastructures, services and applications : 8th European workshop, EuroPKI 2011, Leuven, Belgium, September 15-16, 2011, Revised Selected Papers - Pashalidis, Andreas; Pernul, Günther; Petkova-Nikova, Svetla (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th European Workshop on Public Key Infrastructures, Services and Applications, EuroPKI 2011, held in Leuven, Belgium in September 2011 - co-located with the 16th European Symposium on Research in Computer Security, ESORICS 2011. The 10 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 27 submissions. The papers are organized in topical sections on authentication mechanisms, privacy preserving techniques, PKI and secure applications.